Bloodsucking fiends ebook A love story. - Moore, Christopher (Love Story, 2009)
Jody never asked to become a vampire. But when she wakes up under an alley Dumpster with a badly burned arm, an aching back, superhuman strength, and a distinctly Nosferatuan thirst, she realizes the decision has been made for her. Making the transition from the nine-to-five grind to an eternity of nocturnal prowlings is going to take some doing, however, and that's where C. Thomas Flood fits in. A would-be Kerouac from Incontinence, Indiana, Tommy (to his friends) is biding his time night-clerking and frozen-turkey bowling in a San Francisco Safeway. But all that changes when a beautiful undead redhead walks through the door...and proceeds to rock Tommy's life—and afterlife—in ways he never thought possible.